Management of inferior retinal breaks during pars plana vitrectomy for retinal detachment - Tanner, V (2001)
AIMS—To determine whether it is necessary to support inferior retinal breaks with a scleral explant during pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RD). METHODS—A prospective study was carried out on nine eyes of nine consecutive patients undergoing PPV for primary RD with associated inferior retinal breaks and no significant proliferative vitreoretinopathy. RESULTS—Eight eyes were successfully reattached with a single operation. No cases presented with redetachment because of failed closure of the original inferior breaks. CONCLUSIONS—It is not necessary to support inferior retinal breaks with a scleral explant during PPV for primary RD repair in selected cases.